MODIFIKASI ZEOLIT ALAM DENGAN CETILTRIMETILAMMONIUM BROMIDA SEBAGAI ADSORBEN NO3 - DAN Pb(II) - , NADIA FARISUNA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Modification of natural zeolite with cetyltrimethylammonium bromide (CTAB) as an adsorbent of NO3 - and Pb(II) has been studied. The research was started by the activation of the natural zeolite using 3 M HCl solutions. Then, the activated zeolite was modified with CTAB at variation of CTAB concentration as much as 1.0, 1.5 and 2.0 times of cation exchange capacity to change the zeolite external surface. The surfactant modified natural zeolite was used to adsorption NO3 - and Pb(II). This material was characterized using a Fourier transform infrared (FTIR) spectrophotometer, X-ray diffractometer (XRD) and determination of cation exchange capacity (CEC), whereas the remaining anion and cation were measured by UV-Vis spectrophotometer and atomic absorption spectrophotometer, respectively. The result showed that the sorption of NO3 - and Pb(II) referred to as Langmuir sorption isotherm. The capacity of CTAB modified natural zeolite on NO3 - and Pb(II) was 0.71 mmol.g-1 and 0.29 mmol.g-1, respectively. The sorption energy of CTAB modified natural zeolite on NO3 - and Pb(II) was 27.21 kJ mol-1 and 35.16 kJ mol-1, respectively. This energy showed that adsorption was categorized as chemisorption. The optimum sorption capacity on NO3 - used CTAB modified natural zeolite whereas the optimum sorption capacity on Pb(II) used activated natural zeolite and natural zeolite.